Conglomeratin: a new antibacterial flavonol derivative from Macaranga conglomerata Brenan (Euphorbiaceae). Issue 23 (1st December 2022) - Hashim, Ibrahim; Onyari, John Mmari; Omosa, Leonidah Kerubo; Maru, Shital Mahindra; Nchiozem-Ngnitedem, Vaderament-A; Karpoormath, Rajshekhar
Abstract: A new prenylated kaempferol, conglomeratin (1 ), alongside 7 known compounds including flavonoids (2 and 3 ), ellagic acid derivatives (4 and 5 ), triterpenoids (6 and 7 ), and a coumarin (8 ) were isolated from the leaves (1 − 5 ) and stem bark (6 − 8 ) of Macaranga conglomerata . Their structures were elucidated using spectroscopic and spectrometric techniques. The antibacterial assay was performed using disc diffusion method against Gram-positive and Gram-negative microorganisms. Compound 1 was significantly active against Pseudomonas aeruginosa ATCC 27853 (MIC = 7.8 µg/mL) and moderately active towards Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Klebsiella pneumoniae ATCC 31488 (MIC = 62.5 µg/mL). Compound 2 showed potency against P. aeruginosa ATCC 27853 (MIC = 1.0 µg/mL) while 4 and 7 were selective towards K. pneumoniae ATCC 31488 (MIC = 7.8 and 1.0 µg/mL, respectively). These findings suggest that prenylation of flavonoids may contribute to improving their broad-spectrum antimicrobial activities. Graphical Abstract: UF0001